Fatwa MUI tentang Penyimpangan Ajaran Islam dan Tindakan Pelanggaran Kebebasan Berkeyakinan - Ari Wibowo, Rahmad (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This study focuses on the contribution of religious fatwa MUI on the situation of religious life are colored by various types of discrimination, intolerance, and even violence based on religion. This study found that religious fatwas of the MUI, in practice it is used as a foothold by state officials to violate the freedom of religion/belief. Riskly, legal policy is no longer based on the constitution and the law, but the MUI fatwa. These conditions have spawned authoritarian government legitimized by religious views. On the other hand the fatwa provide religious life situations are colored by different types of discrimination, intolerance, and even violence based on religion.